From Sacred Entity to Secular Resource: The Transformation of Water Values in an Ecotheological Perspective - Nency Aprilia Heydemans; Frieska Putrima Tadung; Valentino Wariki (Institut Kristen Teologi Real Batam, 2026)
Water holds a significant position not only as an ecological resource but also as a spiritual and sacred symbol within human societies. However, modernization, rationalization, and economic orientation have driven a transformation in the meaning of water, shifting it from a sacred and relational understanding toward a more secular, instrumental, and exploitative perspective. This study aims to analyze the transformation of water meanings in modern society and to examine the role of the church in fostering ecological awareness through an ecotheological perspective. The research employs a qualitative method with a library research approach, analyzing various literature related to the sacredness of water, secularization, ecological crisis, and ecotheological thought. The findings indicate that in traditional societies, water is perceived as part of a spiritual reality maintained through customary values, rituals, and collective ecological practices. However, the rise of a modern paradigm based on instrumental rationality has reduced water to an economic commodity, contributing to environmental degradation, particularly through livestock activities and declining ecological awareness in society. Therefore, the church plays a strategic role as an agent of value transformation, bridging local cultural heritage, scientific knowledge, and theological principles concerning creation care. This role is expressed through faith-based education, strengthening ecological ethics, reinterpreting the sacred value of water, environmental advocacy, and the development of ecotheology-based educational curricula within the church. This awareness emerges from the church’s calling to embody a contextual theological praxis in responding to ecological crises and to affirm that water protection is an integral part of Christian responsibility toward the sustainability of life. Abstrak Air memiliki posisi penting tidak hanya sebagai sumber daya ekologis, tetapi juga sebagai simbol spiritual dan sakral dalam kehidupan masyarakat. Namun, modernisasi, rasionalisasi, dan orientasi ekonomi telah mendorong terjadinya transformasi nilai air dari yang semula dipahami secara sakral dan relasional menjadi semakin sekuler, instrumental, dan eksploitatif. Penelitian ini bertujuan menganalisis perubahan makna air dalam masyarakat modern serta mengkaji peran gereja dalam membangun kesadaran ekologis melalui perspektif ekoteologi. Penelitian menggunakan metode kualitatif dengan pendekatan kepustakaan melalui analisis berbagai literatur mengenai sakralitas air, sekularisasi, krisis ekologis, dan pemikiran ekoteologi. Hasil penelitian menunjukkan bahwa dalam masyarakat tradisional, air dipandang sebagai bagian dari realitas spiritual yang dijaga melalui nilai adat, ritual, dan praktik ekologis kolektif. Akan tetapi, berkembangnya paradigma modern yang berorientasi pada rasionalitas instrumental menyebabkan air direduksi menjadi komoditas ekonomi, sehingga memicu pencemaran lingkungan, terutama akibat aktivitas peternakan dan lemahnya kesadaran ekologis masyarakat. Oleh sebab itu, gereja memiliki peran strategis sebagai agen transformasi nilai yang mampu menjembatani warisan budaya lokal, pengetahuan ilmiah, dan prinsip teologis tentang pemeliharaan ciptaan. Peran tersebut diwujudkan melalui pendidikan iman, penguatan etika ekologis, reinterpretasi nilai sakral air, advokasi lingkungan, dan pengembangan kurikulum pendidikan gerejawi berbasis ekoteologi. Kesadaran ini berangkat dari visi gereja yang dipanggil untuk menghadirkan praksis teologis yang kontekstual dalam merespons krisis ekologis serta membangun kesadaran bahwa menjaga air merupakan bagian integral dari tanggung jawab iman Kristen terhadap keberlanjutan kehidupan.